FORHANDLING OG DOKUMENTATION: Traditionel lov i Øvreægypten - Nielsen, H. C. Korsholm (Tidsskriftet Antropologi, 1998)
C. Korsholm Nielsen: Negotiation and Documentation. Customary Law in Upper Egypt This article is concemed with customary law in a district in Upper Egypt. It is based on an interpretation of fifty documents (mahadar al-sulh) issued within the last 25 years in connection with the settling of disputes among the people of the area. The documents were collected during ethnographic field research carried out from 1994 until 1996. The article describes the documents, their content, and the traditional reconciliation councils (majålis al-sulh) which issue them, and argues, that although the introduction of documents - and thereby “writing” - into the reconciliation process could be expected to alter the tradition, it seems that the documents are so closely related to singular and unique cases that no ostensible change is taking place. The tradition is still transmitted orally and depends on the experience of individual men. The documents, rather, are introduced as mnemonic devices related to singular cases and do not constitute a body of legal text.